2004
DOI: 10.1021/bi035904m
|View full text |Cite
|
Sign up to set email alerts
|

Expression, Purification, and Characterization of Bacillus subtilis Cytochromes P450 CYP102A2 and CYP102A3:  Flavocytochrome Homologues of P450 BM3 from Bacillus megaterium

Abstract: The cyp102A2 and cyp102A3 genes encoding the two Bacillus subtilis homologues (CYP102A2 and CYP102A3) of flavocytochrome P450 BM3 (CYP102A1) from Bacillus megaterium have been cloned, expressed in Escherichia coli, purified, and characterized spectroscopically and enzymologically. Both enzymes contain heme, flavin adenine dinucleotide (FAD) and flavin mononucleotide (FMN) cofactors and bind a variety of fatty acid molecules, as demonstrated by conversion of the low-spin resting form of the heme iron to the hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
102
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(102 citation statements)
references
References 60 publications
(91 reference statements)
0
102
0
Order By: Relevance
“…see Ref. 73). The physiological function of P450 BM-3 still remains unclear, although a role in bacterial quorum sensing mediated by oxidative inactivation of acylhomoserine lactones has been proposed (74).…”
Section: P450-redox Partner Fusion Proteinsmentioning
confidence: 95%
“…see Ref. 73). The physiological function of P450 BM-3 still remains unclear, although a role in bacterial quorum sensing mediated by oxidative inactivation of acylhomoserine lactones has been proposed (74).…”
Section: P450-redox Partner Fusion Proteinsmentioning
confidence: 95%
“…Interestingly, whereas ω-C=C bonds increased the regioselectivity towards ω-2, probably due to the activated allylic location of hydroxylation (Table 6, entries 2, 3, and 9), a terminal alkyne-group was demonstrated to deactivate the enzyme by forming an adduct with the heme (Table 6, entry 10) [102,106]. The self-sufficiency of BM3 and its various reactions inspired the characterization of numerous additional CYP102 members, such as CYP102D1 from Streptomyces avermitiliswhich is the only characterized CYP102 outside the Bacillus family [107], CYP102A7 from Bacillus licheniformis (Table 5, entries 11, 30, and 40, Table 6, entries 8 and 13 and Table 7, entries 5 and 10) [78], and CYP102A2 and CYP102A3, both from Bacillus subtilis [108]. Similar as BM3, these family members prefer unsaturated or branched over saturated fatty acids and catalyze the in-chain hydroxylation of all three positions (ω-1, ω-2, and ω-3, e.g.…”
Section: Cyp102mentioning
confidence: 99%
“…The substrate binding and turnover kinetics of both A2 and A3 show sigmoidal behavior, indicating the binding of more than one substrate molecule and possible cooperativity. No sigmoidal behavior has been reported for fatty acid binding or oxidation by P450 BM3 (Gustafsson et al, 2004), though isotope effect studies suggested that both laurate and palmitate could be simultaneously present in the active site (Rock et al, 2003). On the other hand, both homotropic and heterotropic cooperativity have been reported for the oxidation of non-natural substrates such as indole by P450 BM3 (Li et al, 2005;Maurer et al, 2005;Huang et al, 2007), and for drug metabolism by the R47L/ F87V/L188Q mutant in which allosteric effects were also proposed (van Vugt-Lussenburg et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Of the A-subfamily enzymes only CYP102A1, A2, A3, A5 and A7 have been studied in detail. The A2 and A3 enzymes show a preference for branched-chain over linear-chain fatty acids (Budde et al, 2004;Gustafsson et al, 2004;Lentz et al, 2004), A5 prefers polyunsaturated fatty acids over their saturated counterparts , while A7 is broadly similar to the A1 enzyme (Dietrich et al, 2008). The substrate binding and turnover kinetics of both A2 and A3 show sigmoidal behavior, indicating the binding of more than one substrate molecule and possible cooperativity.…”
Section: Introductionmentioning
confidence: 99%